Misunderstanding Aquinas on Law - Riordan, Patrick (New blackfriars, 2025)
This article investigates how two eminent scholars, the French cultural historian Rémi Brague and the American professor of Government J.Budziszewski misunderstand Aquinas on law. It explores the possible reasons for their misunderstandings. In both cases there is a failure to appreciate the theological context and content of what St Thomas has to say about law. Their lack of appreciation for the theological content explains also their individual specific distortions of the account of law. Brague confuses eternal law and divine law, which Aquinas explicitly distinguishes, and applies an abstract notion of the divine which heapplies not only to medieval Christian texts, but also to Greek, Egyptian, Jewish, and Islamic ideas on law. Budziszewski imposes on St Thomas’s classification of types of law the logical structure of genus and species, despite acknowledging that Aquinas avoids this language. The result is that he fails to appreciate the significance of eternal law. Both scholars misapprehend eternal law, and this is due to their ignoring theology. They exemplify a characteristic mistake of treating St Thomas as a philosopher, and his theology as something added on to the philosophical account.